2015
DOI: 10.1159/000438462
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cortisol-to-Cortisone Ratio and Blood Pressure in Severe Obesity before and after Weight Loss

Abstract: Background/Aims: The pathogenesis of obesity-associated hypertension is poorly understood. Serum cortisol-to-cortisone ratio (F/E ratio) is a marker of cortisol metabolism. Our objective was to determine whether the serum F/E ratio is associated with blood pressure (BP) in patients after significant weight loss ( ≥ 15% from baseline weight). Methods: Sera from 43 nondiabetic, severely obese males participating in a weight management program were assayed for F and E by mass spectrometry. We assessed whether cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
3
9
1
Order By: Relevance
“…The negative correlation of DBP and urinary cortisol levels was even part of the multivariable analysis for the prediction of urinary cortisol excretion. Our data are in line with a study on the association of cortisol/cortisone ratio and blood pressure in 43 men before and after weight loss [37]. Despite the much lower sample size, the authors could show a trend toward a negative correlation of basal serum cortisol and DBP in obese men (r = −0.29; p = 0.06) [37].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The negative correlation of DBP and urinary cortisol levels was even part of the multivariable analysis for the prediction of urinary cortisol excretion. Our data are in line with a study on the association of cortisol/cortisone ratio and blood pressure in 43 men before and after weight loss [37]. Despite the much lower sample size, the authors could show a trend toward a negative correlation of basal serum cortisol and DBP in obese men (r = −0.29; p = 0.06) [37].…”
Section: Discussionsupporting
confidence: 91%
“…Our data are in line with a study on the association of cortisol/cortisone ratio and blood pressure in 43 men before and after weight loss [37]. Despite the much lower sample size, the authors could show a trend toward a negative correlation of basal serum cortisol and DBP in obese men (r = −0.29; p = 0.06) [37].…”
Section: Discussionsupporting
confidence: 91%
“…Concentration of cortisol, cortisone, and 11-deoxycortisol was measured using liquid chromatography-tandem mass spectrometry on a Waters XEVO TQ-S system (Waters, Milford, MA, USA) [24, 28]. Glucocorticoid was quantitated using the internal reference in the positive ion mode with multiple reaction monitoring.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a few animal experiments have shown that GCs can inhibit insulin secretion in vitro [22, 23]. Meanwhile, there are epidemiological studies investigating the relationship between F/E and T2DM and prediabetes [19, 24, 25]. Previous research has evidenced the impact of gender differences in the relationship between cortisol and diabetes [26].…”
Section: Introductionmentioning
confidence: 99%
“…36 Another study correlated serum cortisol with cortisone (F/E) and BP with severe obesity before and after weight loss and the alteration of the F/E serum ratio was associated with BP alteration after weight loss. 26 Patients with Human Immunodeficiency Virus (HIV) are at increased risk for metabolic complications (MetS) including SAH and excess cortisol. In this sense, a study was conducted in the Netherlands where they identified that the risk of MetS was higher in HIV-infected patients in the lower-level capillary cortisol group compared to patients with higher levels.…”
Section: Methods (Study Design Population Cortisolmentioning
confidence: 99%